2020
DOI: 10.1002/jsfa.10805
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel antifungal protein produced by Paenibacillus polymyxa isolated from the wheat rhizosphere

Abstract: BACKGROUND Fusarium head blight (FHB) is one of the disasters that seriously harm wheat and other small grain crops. It causes spoilage and mildew of the grain leading to a significant decline in the yield and quality of the grain. This research aimed to isolate antagonistic bacteria to purify antifungal proteins. A strain was isolated from the rhizosphere of healthy wheat in a wheat field affected by a severe FHB epidemic. This isolated strain was tentatively identified as Paenibacillus polymyxa 7F1, which di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Several protein fractions had protein molecular masses of about 37 kDa and 60 kDa (Figure 6). The results were similar to the electrophoretic results of Ran [31].…”
Section: Analysis Of Protein Concentration Sds-page Electrophoresis R...supporting
confidence: 88%
See 2 more Smart Citations
“…Several protein fractions had protein molecular masses of about 37 kDa and 60 kDa (Figure 6). The results were similar to the electrophoretic results of Ran [31].…”
Section: Analysis Of Protein Concentration Sds-page Electrophoresis R...supporting
confidence: 88%
“…Several protein fractions had protein molecular masses of about 37 kDa and 60 kDa (Figure 6). The results were similar to the electrophoretic results of Ran [31]. As can be seen in Figure 7, after treatment with antifungal proteins, the mycelial morphology of A. tubingensis shriveled and underwent significant breakage and fragmentation.…”
Section: Analysis Of Protein Concentration Sds-page Electrophoresis R...supporting
confidence: 85%
See 1 more Smart Citation
“…Compared with spore germination and germ tube elongation, hyphae growth phase was more sensitive to the effect of AF01 culture filtrate, while germ tube growth was less affected, which is in agreement with other findings on the antifungal activity of P. polymyxa and other Paenibacillus spp. against fungal species such as Cylindrocarpon destructant , Rhizoctonia solani , Fusarium sp., Sclerotinia sclerotiorum , Pythium ultimum ( Bae et al, 2004 ), Colletotrichum gloeosporioides ( Ran et al, 2021 ), Pseudoperonospora cubensis , B. cinerea , Phytophthora capsica ( Kim et al, 2009 ) and Magnaporthe oryzae ( Ali et al, 2021 ). Microscopic observations revealed that P. polymyxa AF01 hampered the fungus spore causing mycelial tip enlargement, protoplast cleavage and abnormal morphological alternations of the spores.…”
Section: Discussionmentioning
confidence: 99%
“…These factors led to reduced biofungicide residual activity, requiring multiple applications over a growing season, which increased production costs (do Nascimento et al, 2022). But, biological fungicides are still attracting more and more attention worldwide because of its effective, safe and environment‐friendly advantages (Luo et al, 2019; Ran et al, 2020; Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%